A phylogenetic analysis of Synoeca de Saussure, 1852, A neotropical genus of social wasps (Hymenoptera: Vespidae: Epiponini) - Andena, Sergio R. (2009)
Characters of adult morphology, male genitalia, and nest architecture are combined in a cladistic analysis of the neotropical paper wasp genus Synoeca. The single resulting cladogram supports the monophyly of genus. The species are related as follows: S. chalibea (S. virginea (S. septentrionalis (S. surinama S. cyanea))). A new identification key is also presented. © 2009 New York Entomological Society.